2012
DOI: 10.1371/journal.pone.0041419
|View full text |Cite
|
Sign up to set email alerts
|

Input-Dependent Wave Attenuation in a Critically-Balanced Model of Cortex

Abstract: A number of studies have suggested that many properties of brain activity can be understood in terms of critical systems. However it is still not known how the long-range susceptibilities characteristic of criticality arise in the living brain from its local connectivity structures. Here we prove that a dynamically critically-poised model of cortex acquires an infinitely-long ranged susceptibility in the absence of input. When an input is presented, the susceptibility attenuates exponentially as a function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In physics, the relationship between the spatial and temporal frequencies in a system is known as the dispersion relation. Yan and Magnasco [ 27 ] have shown that the dispersion relation of the system considered in this paper and described by Eq (1) is elliptical, c 2 k 2 + ω 2 = 1, where k and ω are the spatial and temporal frequencies, respectively, and c is a constant. If our theory is correct, multielectrode array recordings in V1 should reveal elliptic dispersion relations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In physics, the relationship between the spatial and temporal frequencies in a system is known as the dispersion relation. Yan and Magnasco [ 27 ] have shown that the dispersion relation of the system considered in this paper and described by Eq (1) is elliptical, c 2 k 2 + ω 2 = 1, where k and ω are the spatial and temporal frequencies, respectively, and c is a constant. If our theory is correct, multielectrode array recordings in V1 should reveal elliptic dispersion relations.…”
Section: Discussionmentioning
confidence: 99%
“…Let be the activity vector for a network of neurons which evolve in time according to the normal form equation: In this model, originally proposed by Yan and Magnasco [ 27 ], neurons interact with one another through a skew-symmetric connectivity matrix A . The cubic-nonlinear term in the model is purely local and does not couple the activity states of distinct neurons, while the external input to the system may depend on time and have a complex spatial pattern.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, a recent study provides fMRI data supporting the latter hypothesis [ 68 ]. By demonstrating that activation of GlyRs along the L5PyNs dendrite enables efficient shunt of synaptic inputs while maintaining the E-I balance intact, the present study shed light on a mechanism that likely participates in the selective wave attenuation of sensory inputs, known to be necessary for the adaptation of inputs intensity to visual processing [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previoiusly argued that homeostatic mechanisms, such as those seeking to balance excitation and inhibition, will result in many dynamical modes of the system posing themselves close to the boundary between stability and instability [15]. Near the onset of instability, the spatial layout of such dynamical modes is determined as eigenvectors of a connectivity matrix [16]; their transient activation is then consistent with the eigenvalue of such an eigenvector being driven through the instability line, and back [14,17].…”
Section: Introductionmentioning
confidence: 99%